1995
DOI: 10.1073/pnas.92.8.3110
|View full text |Cite
|
Sign up to set email alerts
|

Proline-rich sequences that bind to Src homology 3 domains with individual specificities.

Abstract: To study the binding specificity of Src homology 3 (SH3) domains, we have screened a mouse embryonic expression library for peptide fragments that interact with them. Several clones were identified that express fragments of proteins which, through proline-rich binding sites, exhibit differential binding specificity to various SH3 domains. Src-SH3-specific binding uses a sequence of 7 aa of the consensus RPLPXXP, in Protein-protein interactions are central events in cellular signal transduction. These interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
191
1
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(197 citation statements)
references
References 34 publications
2
191
1
3
Order By: Relevance
“…Because fragment analysis has demonstrated that the COOH-terminal portion of synapsin I is involved in binding the SH3 domains of c-Src (this Relative to the homogenate, Src was enriched in highly purified vesicle fractions, and its association with the vesicle membrane was not affected by the salt treatment used to deplete synapsin I. H, homogenate; S1, postnuclear supernatant; S2, supernatant of P2; P2, crude synaptosomes; LP1, crude synaptic plasma membranes; LS1, supernatant of LP1; LP2, crude synaptic vesicles; LS2, synaptosol; SG2, synaptic vesicles; SG4, small synaptic membranes; USV, untreated synaptic vesicles; STSV, salt-treated synaptic vesicles. Analysis by screening libraries of phage-displayed or synthetic peptides has shown that the c-Src-SH3 domain exhibits a preference for the class I binding motif, RPLPPLP (26)(27)(28)(29), although it can also bind to class II ligands (28,30). In this respect, class II ligands have been reported to be more promiscuous in their binding to SH3 domains than class I ligands, and they exhibit more flexibility in the distance between the PXXP motif and the neighboring arginine residue, a property that can contribute to a broader specificity of this interaction (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…Because fragment analysis has demonstrated that the COOH-terminal portion of synapsin I is involved in binding the SH3 domains of c-Src (this Relative to the homogenate, Src was enriched in highly purified vesicle fractions, and its association with the vesicle membrane was not affected by the salt treatment used to deplete synapsin I. H, homogenate; S1, postnuclear supernatant; S2, supernatant of P2; P2, crude synaptosomes; LP1, crude synaptic plasma membranes; LS1, supernatant of LP1; LP2, crude synaptic vesicles; LS2, synaptosol; SG2, synaptic vesicles; SG4, small synaptic membranes; USV, untreated synaptic vesicles; STSV, salt-treated synaptic vesicles. Analysis by screening libraries of phage-displayed or synthetic peptides has shown that the c-Src-SH3 domain exhibits a preference for the class I binding motif, RPLPPLP (26)(27)(28)(29), although it can also bind to class II ligands (28,30). In this respect, class II ligands have been reported to be more promiscuous in their binding to SH3 domains than class I ligands, and they exhibit more flexibility in the distance between the PXXP motif and the neighboring arginine residue, a property that can contribute to a broader specificity of this interaction (28,31).…”
Section: Discussionmentioning
confidence: 99%
“…SH2 domains bind phosphotyrosine moieties (Pawson, 1995). SH3 domains, which often accompany SH2 domains, recognize proline-rich sequences in target proteins (Alexandropoulos et al, 1995;Mayer and Baltimore, 1993;Pawson, 1995). Adapter proteins, including Crk, Nck and Grb2, are composed almost exclusively of SH2 and SH3 domains and lack any enzymatic or other functional activities (Mayer and Baltimore, 1993;Pawson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…At least one peptide without a basic residue, actually with a tyrosine, at position P -3 was described that binds to the SH3 domain of Fyn. The 3BP2-derived peptide PPAYPPPPVP, which is a physiological Abl ligand, is able to bind Fyn SH3 (49), although this may not be physiologically relevant (50).…”
Section: Resultsmentioning
confidence: 99%